2016
DOI: 10.1038/srep28703
|View full text |Cite
|
Sign up to set email alerts
|

The dynamics of the HIV epidemic among men who have sex with men (MSM) from 2005 to 2012 in Shenzhen, China

Abstract: HIV-1 epidemics among MSM are a major public health concern in China, especially in large cities. This study sought to better understand the dynamics of HIV molecular epidemiology among MSM in Shenzhen, a rapidly developing city with over 13.8 million people. HIV-1 pol sequences were obtained from 996 (53.5%) of 1862 HIV-infected MSM and 403(9.0%) of 4498 heterosexuals and injection drug users in Shenzhen, China from 2005-2012. Eight HIV-1 subtypes and some inter-subtype recombinants were identified among samp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

8
49
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 62 publications
(60 citation statements)
references
References 34 publications
8
49
0
Order By: Relevance
“…Our evolutionary analyses, based on 209 partial pol gene sequences of HIV-1 CRF55_01B that included province of origin and year of sampling, confirmed that this subtype had spread widely within China ( Supplementary Table S1) 7,8,28 . Our estimates of the evolutionary rate for CRF55_01B was reassuringly consistent across different methods and models.…”
Section: Discussionsupporting
confidence: 53%
“…Our evolutionary analyses, based on 209 partial pol gene sequences of HIV-1 CRF55_01B that included province of origin and year of sampling, confirmed that this subtype had spread widely within China ( Supplementary Table S1) 7,8,28 . Our estimates of the evolutionary rate for CRF55_01B was reassuringly consistent across different methods and models.…”
Section: Discussionsupporting
confidence: 53%
“…In this study, genetic distances ≤0.015 and ≤ 0.014 were set as cutoff values for CRF01_AE and CRF07_BC, respectively. The value is similar to the value always used for construction of the subtype B transmission network [28][29][30]. To date, very few studies have been performed on the CRF07_BC transmission network because very small genetic distances were always found between CRF07_BC strains from different individuals.…”
Section: Discussionmentioning
confidence: 55%
“…In total, 1.2% of the samples were resistant to nucleoside reverse transcriptase inhibitors (NRTIs), Phylogenetic analysis identified four recombinant subtypes CRF01_AE, CRF07_BC, CRF08_BC, CRF55_01B and two subtypes B, C. Chengdu is an area with predominance of CRF01_AE and CRF08_BC, indicating a distinct subtypic heterogeneity compared to what has been shown in other regions [20,21]. For instance, about half of the subtypes were identified as CRF08_BC (47.4%) among the recently infected population in Yunan [22] and CRF07_BC was the predominant strain in Xinjiang Province [23].…”
Section: Categories Of Antiretroviral Drugs and Susceptibility Of Drumentioning
confidence: 96%